Pendayagunaan ZIS Di Baznas Kabupaten Wonosobo Relevansinya Terhadap Program Sustainable Development Goals - Istiyanti, Tri (Program Studi Hukum Ekonomi Syariah, 2023)
BAZNAS Wonosobo Regency is a zakat management institution formed by the government, consisting of government and community elements whose scope of management is regarding planning, collection, utilization and control. Based on this scope, from the types of programs carried out by the way zakat works, it is inevitable that it has a clear slice of the objectives of achieving the Sustainable Development Goals (SDGs). This study resulted in the following conclusions. First, zakat management is an activity of planning, implementing and coordinating the collection, distribution and utilization of zakat, which aims to increase the effectiveness and efficiency of services in managing zakat and increasing the benefits of zakat to realize community welfare and poverty alleviation. Second, from the results of the discussion, there is the Wonosobo Regency BAZNAS program relevant to the SDGs, namely 7 Goals, 13 Targets and 16 Indicators namely No Poverty, No Hunger, Healthy and Prosperous Life, Quality Education, Clean Water and Proper Sanitation, Decent Work and Economic Growth, and Cities and Sustainable Settlements. And there is a sharia maqasid value in the Wonosobo Taqwa program which is not included in the SDGs program.